ANALISIS RESIKO KESELAMATAN DAN KESEHATAN KERJA PADA DEPARTEMEN MOULDING DI PT HLN RUBBER BATAM - handoko, edi; Arista, Anggia (LPPM Universitas Putera Batam, 2023)
PT HLN Rubber Batam is a molding company engaged in the production and management of Rubber Cromets/rubber into semi-finished goods (seal rubber) which will be redistributed to other companies so that it becomes a marketable product. Based on data from 2020-2022 there have been several cases of work accidents, namely, when cutting NBR material (hard material) so that it injured the fingers resulting in several stitches on the fingers totaling 3 people, another work accident was injuries to the eyelids due to not wearing safety glasses when they want to work totaling 7 people. To reduce the number of work accidents, it is necessary to carry out work accident prevention programs, namely by implementing Risk Management to find out the hazards and potential risks that exist in the workplace. The hazard identification process is a part of risk management. Risk assessment includes hazard identification, hazard potential analysis, risk assessment, risk control, as well as monitoring and evaluation. In the process of identifying and analyzing potential hazards, the Hazard and Operability Study (HAZOP) method can be used.